IN FINANCE OF THE CRISIS ROLE AND HIS MANIFESTATION TO BE - Abdurahmanov Abdulaziz Mahmudovich (PT ANTIS International Publisher, 2024)
Finance crisis concept news not. Him initial surface came times to the 17th century go is worn From the 17th century to the present until times a lot in finance crises , crisis cases to the eye thrown away Crisis and about him briefly information this in the article statement i did In economics happened giving internal and external changes of course never who indifferent does not leave Because this effects country development enough for level important is considered Current at the time economic crises , especially to young people extremely big negative effect is showing . The unemployed main part young people organize is doing